Ergonomic, epistemological and existential challenges of integrating digital tools into school mathematics. Issue 1 (March 2022) - Ruthven, Kenneth
Despite half a century of sustained advocacy and effort, the degree to which use of digital mathematical tools has become integral to the practice of school mathematics remains limited. The main sections of this paper identify three fundamental dimensions of challenge to such integration, illustrating the kinds of adaptation required. The ergonomic dimension relates to environmental and cognitive features which structure interaction between humans and digital tools in the everyday practice of school mathematics. The epistemological dimension relates to disciplinary and didactical knowledge available to guide use of digital tools in school mathematics. The existential dimension concerns conceptions of self and subject which shape use (and non-use) of such tools. In the light of this framework, a further section reviews the impact of the recent pandemic shock on use of digital tools in school mathematics.